The Implementation Impact of IFRS 16: Leases on JSE Listed Technology and Telecommunication Companies Using a Constructive Capitalisation Model: Array - Cumming, Carley; Galt, Harold (The Journal of Accounting and Management, 2020)
Abstract: Objectives: This study used a constructive capitalisation model to assess the likely impact IFRS 16 will have on a company’s financial statements and ratios when it is implemented; this article analysed this expected impact on the financial position, financial performance and market ratios for technology and telecommunication companies. Prior work: This study builds on prior lease accounting research. Approach: A two sample (paired) t-test was used to test the magnitude of the change that occurred in the financial statement ratios after applying the constructive capitalisation model. The two samples consisted of the financial ratios before operating leases were capitalised, compared to the financial ratios post-capitalisation for JSE listed technology and telecommunication companies Results: The analysis of the data revealed that when the constructive capitalisation model is applied it results in changes in the financial position, financial performance and market ratios for both the technology and telecommunication populations. Despite a number of these changes being significant for the technology population, the changes for the telecommunication population were not considered significant. Implications: Those companies that have material operating leases should assess what impact IFRS 16 will have on their financial statements and financial ratios before the new lease standard IFRS 16 comes into effect. Value: For entities that have a significant number of operating leases, IFRS 16 is anticipated to materially affect the figures in the financial statements, capital structure, as well as liquidity and profitability ratios. Numerous stakeholders rely on these reported figures and ratios when making entity-related decisions.